An Electrochemical Sensor for the Simultaneous Detection of Pb2+ and Cd2+ in Contaminated Seawater Based on Intelligent Mobile Detection Devices - Zizi Zhao; Wei Qu; Chengjun Qiu; Yuan Zhuang; Kaixuan Chen; Yi Qu; Huili Hao; Wenhao Wang; Haozheng Liu; Jiahua Su (Chemosensors)
Excessive levels of Pb2+ and Cd2+ in seawater pose significant combined toxicity to marine organisms, resulting in harmful effects and further threatening human health through biomagnification in the food chain. Traditional methods for detecting marine Pb2+ and Cd2+ rely on laboratory analyses, which are hindered by limitations such as sample degradation during transport and complex operational procedures. In this study, we present an electrochemical sensor based on intelligent mobile detection devices. By combining G-COOH-MWCNTs/ZnO with differential pulse voltammetry, the sensor enables the efficient, simultaneous detection of Pb2+ and Cd2+ in seawater. The G-COOH-MWCNTs/ZnO composite film is prepared via drop-coating and is applied to a glassy carbon electrode. The film is characterized using cyclic voltammetry, electrochemical impedance spectroscopy, and scanning electron microscopy, while Pb2+ and Cd2+ are quantified using differential pulse voltammetry. Using a 0.1 mol/L sodium acetate buffer (pH 5.5), a deposition potential of −1.1 V, and an accumulation time of 300 s, a strong linear correlation was observed between the peak response currents of Pb2+ and Cd2+ and their concentrations in the range of 25–450 µg/L. The detection limits were 0.535 µg/L for Pb2+ and 0.354 µg/L for Cd2+. The sensor was applied for the analysis of seawater samples from Maowei Sea, achieving recovery rates for Pb2+ ranging from 97.7% to 103%, and for Cd2+ from 97% to 106.1%. These results demonstrate that the sensor exhibits high sensitivity and stability, offering a reliable solution for the on-site monitoring of heavy metal contamination in marine environments.